2019
DOI: 10.1155/2019/5420624
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effect of Embryonic Stem Cells Reducing Lipid Peroxidation in Kidney Injury Induced by Cisplatin

Abstract: Introduction. The acute kidney injury (AKI) is characterized by a sudden glomerular filtration reduction. Renal or intrinsic causes of AKI include nephrotoxicity induced by exogenous agents like cisplatin, which causes oxidative stress altering the biochemical process and leading to apoptosis. Therefore, this research is aimed at analyzing the embryonic stem cells (ESC) nephroprotective effect in AKI induced by cisplatin, employing genetic, phenotypic, and microspectroscopic techniques. Methods. Thirty mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…To investigate the protective effects of RIPC on Cis-induced AKI mice, we constructed a RIPC pretreatment animal model following the procedure in Figure 1(a). It was frequently observed that the Cis-induced AKI mice exhibit the elevation of serum creatinine (CRE) and blood urea nitrogen (BUN) level, which are closely linked to renal function [28, 29]. Indeed, we observed that the serum CRE and BUN concentrations were significantly increased to 2.9- and 4.3-fold of Con group after Cis treatment (20 mg/kg) (Figures 1(b) and 1(c)), respectively, suggesting the kidney and animals receive a serious damage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the protective effects of RIPC on Cis-induced AKI mice, we constructed a RIPC pretreatment animal model following the procedure in Figure 1(a). It was frequently observed that the Cis-induced AKI mice exhibit the elevation of serum creatinine (CRE) and blood urea nitrogen (BUN) level, which are closely linked to renal function [28, 29]. Indeed, we observed that the serum CRE and BUN concentrations were significantly increased to 2.9- and 4.3-fold of Con group after Cis treatment (20 mg/kg) (Figures 1(b) and 1(c)), respectively, suggesting the kidney and animals receive a serious damage.…”
Section: Resultsmentioning
confidence: 99%
“…It was well documented that tubular epithelial cell apoptosis plays crucial roles in the pathogenesis of Cis-induced AKI [30, 31]. To further demonstrate that RIPC protects the kidney from Cis-induced AKI in a miR-144-mediated manner, we manipulated the expression of miR-144 using a well-worked antago-miR [28, 29]. Firstly, we checked the expression of miR-144 using real-time qPCR and found its expression was dramatically downregulated (Figure 4(a)).…”
Section: Resultsmentioning
confidence: 99%
“…Glomerulosclerosis or collapsed glomeruli were not observed in RFI mice treated with mESCs; even some regeneration data were found characterized by large nuclei with prominent [37]. Mata-Miranda et al suggested the beneficial effects of mESCs on AKI were related to the reduction of lipid peroxidation [38].…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%
“…Oxidative injury mediated by lipid peroxidation is an unfavorable factor for AKI [ 85 ], while lipid peroxidation inhibition can alleviate kidney injury [ 86 ]. One month before Dixon proposed ferroptosis, some researchers found that deferoxamine (DFO), which was not listed as a ferroptosis inhibitor then, could inhibit lipid peroxidation and renal tubular epithelial cell necrosis to prevent renal failure [ 87 ].…”
Section: Ferroptosis and Akimentioning
confidence: 99%